PERAN STRATEGIS PENYULUH PERIKANAN DALAM PENERBITAN KARTU ELEKTONIK PAS KECIL DI KABUPATEN SIKKA - Nona Lanti, Arlinda; Erfin; Roberto Jerun Parera, Guido (Jurnal Biogenerasi, 2025)
This research aims to examine the important role of fisheries instructors in implementing and optimizing the issuance of these cards in Sikka Regency. The research method used is a qualitative descriptive approach with data collection through in-depth interviews, direct observation and document analysis. The research results show that fisheries instructors have three main roles, namely: (1) socializing the program to fishermen, (2) assisting in the administration process of issuing Small E-Pas cards, (3) increasing the ability of fishermen to utilize karu to access government programs. However, challenges such as limited administrative literacy of fishermen and access to remote areas are still the main obstacles. This research concludes that the success of the program is highly dependent on the active role of fisheries instructors, with the need for additional support from local governments to overcome existing obstacles.